Reliability Measurement of Learning Outcome using K-Means Cluster Technique - Rozahi Istambul, Muhammad; Abinowi, Egi (International Journal of Psychosocial Rehabilitation, 2020)
E-learning has begun to be widely used in universities in Indonesia. However, various obstacles are commonly encountered in its implementation, such as infrastructure and learning design. Usually, the problem of providing infrastructure is adjusted to the ability of a university to procure needs according to the conditions in the field. This is very different from the design of e-learning, which demands a change in pedagogical paradigm in the interaction between lecturers and students. Learning outcomes of a single course at the university under study are often not optimal/reliable and tend to indicate passive student participation in face-to-face activities in class. Therefore, the design of e-learning is very important to be made in such a way that the level of student participation becomes higher and results in reliable learning outcomes. Reliability is measured using the K-means cluster technique by monitoring the extent to which students interact when using e-learning facilities.